Cultural History of the South-East Prekmurje in the Early Modern Period - Sedar, Klaudija (Anali PAZU HD, 2022)
This article presents some of the most visible cultural and historical features of the South-East Prekmurje in the 17th and 18th century. Since the spiritual and cultural development in the southern part of Prekmurje was different from the one in the northern part, due to the canonical and political borders in the course of the turning points in history, I was interested in how all this was reflected at the cultural level in the southern Prekmurje. It has been established that in this period religion played a major role in people’s lives in Prekmurje, complementarily strongly linked with the language and national identity. Furthermore, a severe cultural poverty was reflected in this part of Prekmurje, but was comparable with the situation at that time in the wider European area.